Managers and productivity differences - Nezih Guner; Andrii Parkhomenko; Gustavo Ventura (Luxembourg Income Study (LIS), 2015)
We document that mean earnings of managers grow faster than for non managers over the life cycle for a group of high-income countries. Furthermore, we find that the growth of earnings for managers (relative to non managers) is positively correlated with output per worker across these countries. We interpret this evidence through the lens of an equilibrium span-of-control model where managers invest in their skills. Central to our analysis is a complementarity between skills and investments in the production of new managerial skills that ampli.es initial differences in skills over the life cycle. We discipline model parameters with observations on managerial earnings and the size-distribution of plants in the United States, and then use our framework to quantify the importance of (i) lower exogenous productivity differences, and (ii) the size-dependent distortions emphasized in recent literature. Our findings show that both of these factors reduce managerial investments and lead to a lower earnings growth of managers relative to non managers. We also specialize the framework to evaluate the relative contribution of exogenous productivity versus size-dependent distortions for output and plant-size differences between the U.S. and Japan. Our results show that exogenous productivity differences account for about 80% of the output gap between these two countries. Size-dependent distortions are responsible for nearly all differences in plant size.
Keywords: E23; E24; J24; M11; O43; O47; 330; Managers; Distortions; Size; Skill Investments; Productivity Differences